Unilateral optic neuritis, scleritis and exudative retinal detachment due to recurrent orbital pseudotumor - Chaudhry, Imtiaz A. (Elsevier, 2012)
Idiopathic orbital inflammation, also known as orbital pseudotumor, describes a spectrum of idiopathic, non-neoplastic, non-infectious, space-occupying orbital lesions without identifiable local or systemic cause. The condition occurs mainly in young adults who may present with acute pain, proptosis, chemosis and limitations of extraocular movements. Decreased vision due to optic nerve infiltration and macular edema as a result of scleritis is less common sequel of orbital pseudotumor. Herein, we present a case of unilateral orbital pseudotumor in a young male who presented with chief complaints of painful decreased vision which was attributed to optic neuritis and macular edema as a result of scleritis. Imaging studies were helpful in the establishment of the correct diagnosis and patient’s complaints improved with administration of systemic corticosteroids.